Colossal Magnetoresistance of (La₁₋ₓ Aₓ)₀.₆₇ Ca₀.₃₃MnO₃ (A=Sn, Sm and Er) Perovskite - Gebrel, Zohra Ali Mohamed (2003)
In this work, the colossal magnetoresistance (CMR) of (Lal-xSnx)2/3CaI/3MnO3 [LSnCMO], (Lal-xSmx)2/3Cal/3MnO3 LSmCMO] and (Lal-xErx)2/3CaI/3MnO3 [LErCMO] ceramics samples, with x=O.O to 0.4 were prepared by solid-state reaction technique. The structure, magnetic and electrical properties of the samples were investigated. The x-ray diffraction (XRD) spectrum for all the samples exhibit orthorhombic distorted and single-phase perovskite structures with the presence of some minor impurities. The magnetic properties were studied by measuring the susceptibility of the samples as a function of temperature at various magnetic fields. Ferromagnetic-paramagnetic phase transition temperature, Te was determined for low doping concentration. The Curie temperature, Tc shifts to lower temperature as tin, samarium and erbium content was increased, indicating the loss of ferromagnetic order. For high tin content, the classical ferromagnetic order disappears and a cusp peak anomaly appears at 87 K, 68 K, 61 K and 55 K for x=O.l, 0.2, 0.3 and 0.4 respectivel